High-Intensity Intermittent Training in Hypoxia: A Double-Blinded, Placebo-Controlled Field Study in Youth Football Players. Issue 1 (January 2015) - Brocherie, Franck; Girard, Olivier; Faiss, Raphael; Millet, Grégoire P.
Abstract : Abstract: Brocherie, F, Girard, O, Faiss, R, and Millet, GP. High-intensity intermittent training in hypoxia: A double-blinded, placebo-controlled field study in youth football players. J Strength Cond Res 29(1): 226–237, 2015—This study examined the effects of 5 weeks (∼60 minutes per training, 2 d·wk −1 ) of run-based high-intensity repeated-sprint ability (RSA) and explosive strength/agility/sprint training in either normobaric hypoxia repeated sprints in hypoxia (RSH; inspired oxygen fraction [FI O2 ] = 14.3%) or repeated sprints in normoxia (RSN; FI O2 = 21.0%) on physical performance in 16 highly trained, under-18 male footballers. For both RSH ( n = 8) and RSN ( n = 8) groups, lower-limb explosive power, sprinting (10–40 m) times, maximal aerobic speed, repeated-sprint (10 × 30 m, 30-s rest) and repeated-agility (RA) (6 × 20 m, 30-s rest) abilities were evaluated in normoxia before and after supervised training. Lower-limb explosive power (+6.5 ± 1.9% vs. +5.0 ± 7.6% for RSH and RSN, respectively; both p < 0.001) and performance during maximal sprinting increased (from −6.6 ± 2.2% vs. −4.3 ± 2.6% at 10 m to −1.7 ± 1.7% vs. −1.3 ± 2.3% at 40 m for RSH and RSN, respectively; p values ranging from <0.05 to <0.01) to a similar extent in RSH and RSN. Both groups improved best (−3.0 ± 1.7% vs. −2.3 ± 1.8%; both p ⩽ 0.05) and mean (−3.2 ± 1.7%, p < 0.01 vs. −1.9 ± 2.6%, p ⩽ 0.05 for RSH and RSN, respectively) repeated-sprint times, whereas sprint decrement did not change. Significant interactions effects ( p ⩽ 0.05) between condition and time were found for RA ability–related parameters with very likely greater gains ( p ⩽ 0.05) for RSH than RSN (initial sprint: 4.4 ± 1.9% vs. 2.0 ± 1.7% and cumulated times: 4.3 ± 0.6% vs. 2.4 ± 1.7%). Maximal aerobic speed remained unchanged throughout the protocol. In youth highly trained football players, the addition of 10 repeated-sprint training sessions performed in hypoxia vs. normoxia to their regular football practice over a 5-week in-season period was more efficient at enhancing RA ability (including direction changes), whereas it had no additional effect on improvements in lower-limb explosive power, maximal sprinting, and RSA performance.